ChemInform Abstract: Chrotacumines E and F, Two New Chromone‐Alkaloid Analogues from Dysoxylum acutangulum (Meliaceae) Leaves. Issue 3 (21st January 2014) - Lazim, Mohd Izwan Mohd; Ismail, Intan Safinar; Shaari, Khozirah; Latip, Jalifah Abd.; Al‐Mekhlafi, Nabil Ali; Morita, Hiroshi
Abstract Chrotacumines E (I) and F (II) show modest activities as tyrosinase inhibitors.